Genetic Diversity Analysis of the Chinese Daur Ethnic Group in Heilongjiang Province by Complete Mitochondrial Genome Sequencing - Jia, Mansha; Li, Qiuyan; Zhang, Tingting; Dong, Bonan; Liang, Xiao; Fu, Songbin; Yu, Jingcui (Frontiers in Genetics, 2022)
Mitochondrial DNA (mtDNA) has the characteristics of maternal inheritance, high mutation rate, high copy number and no recombination. As the most powerful tool for studying the origin and evolution of modern humans, mtDNA has extremely important significance in the research of population genetics and evolutionary genetics. Here we provided new insights into the maternal genetic history of Daur ethnic group by generated complete mitochondrial genomes from a total of 146 Daur individuals in China. We also collected the published complete mitochondrial genome sequences of 5094 individuals from 56 worldwide populations as reference data, to further explored the matrilineal genetic landscape of the Daur ethnic group. Firstly, the haplotype diversity was 0.9943±0.0019, nucleotide diversity was 0.0428±0.0210. The neutrality tests of Daur group showed significant negative values and the mismatch distribution curve was obviously distributed in a unimodal pattern. The results showed that Daur ethnic group has a high genetic diversity and may have experienced recent population expansion. In addition, the main haplogroups of Daur population were haplogroup D (31.51%), M* (20.55%), C (10.28%), F (7.53%), B (6.85%), both of which were prevalent to northern China. It probably implied the northern Chinese origin of Daur population. The PCA, FST and phylogenetic analysis results indicated that Daur group formed a cluster with East Asian populations, and had few genetic differences with the populations in northern China. More importantly, we found that disease-related mutation sites of the mitochondrial genome may be related to ethnic groups, which may have important implications for the prevention and occurrence of the specific diseases. Overall, this study revealed the complexity and diversity of the matrilineal genetic background of Daur ethnic group. Meanwhile, it provided meaningful data for the research on the diversity of the human genome.